Problem-Solving Skills and Internalizing Problems in Adolescents - Zakalfikri, Aslam; Widyasari, Dian Caesaria; Karmiyati, Diah; Syakarofath, Nandy Agustin (Gadjah Mada Journal of Psychology (GamaJoP), 2025)
Many changes occur during adolescence, including physical, cognitive, and psychological. They must be addressed appropriately to prevent internalizing problems at this developmental stage. Problem-solving is one of the personal skills that eases the adaptation to drastic developmental changes. Additionally, gender has been found to affect internalizing problems. This study aimed to measure the gender differences in internalizing problems and simultaneously examine the role of problem-solving skills and gender in internalizing problems. Based on simple random sampling, 669 students from eight Muhammadiyah high schools in East Java participated in this study. Data were collected using the Problem-Solving Inventory (PSI), the Strengths and Difficulties Questionnaire (SDQ), and demographic questions. The independent sample t-test results indicated significant gender differences in internalizing problems (t = -5.73, p < .001), in which female adolescents on average scored higher than their male counterparts. The multiple linear regression showed that problem-solving and gender simultaneously contribute to internalizing problems and account for 14% of the variance in internalizing problems. Incorporating the development of gender-based problem-solving skills among adolescents is likely to help prevent internalizing problems.